LATAR BELAKANG SEKS PRANIKAH SEBAGAI PEMICU HAMIL DI LUAR NIKAH DI KALANGAN REMAJA PUTRI DI PAINAN TIMUR KECAMATAN IV JURAI KABUPATEN PESISIR SELATAN - SARI, Novita NILA (Pendidikan Sosiologi, 2014)
This research backgrounded by a lot of daughter stripling that pregnant outside gets married that old of 17 21 years. Pregnant stripling outdoor gets married a lot of happening on adolescent one stills to sit in education stool,but there is also on their behalf has already ended education on their behalf that still sits in their education stool cant drawn out education again. This case a lot of at finds on transition term, vulnerable stripling with changed because they are still labih and cant screen novelty. Beginning of life style, attitude, even behavioural. Suppose on that age stripling stills to sit in education stool as adolescent as another but effect this case causes they cant drawn out education again are not economic its causative dont drawn out education but their own u. This research intent to know free seks background as trigger of pregnancy outside gets married among daughter stripling.This research utilize Fenomenologis theory because motif that interposed by Alfrenz Shcutz, with kualitatifs method and descriptive type. There is informan even this research is adolescent outdoor pregnant one get married that old 17 21 years and is at nagari painan easts, of 19 pregnant stripling outside just get married 9 stripling that accomplish this research criterion and added by supporting informan which is society and society figure 6 informen. Tech that is used blackballs informan be purposive sampling (witting sample pull). Data type that is utilized is primary data and secondary data. Data collecting method is done is observation and interview. analisiss unit data that is utilized is individual with analisis Miless data and Huberman what do consisting of data collecting phase, data reduction, data representation and conclusion pull.Result observationaling to point out that free sex background as trigger of pregnancy outside gets married that at happening among adolescent daughter which is since (1 ). Free love, (2). Its reducing is oldster affection, communication and observation, (3 ). Pacaran Sesuku, (4). Communication media influence, (5). Its reducing is appreciative religions, (6). Dont get science about seks.